How Germany can benefit from the Global Compact for Migration: Opportunities for national reforms and international cooperation - Steffen Angenendt; Anne Koch (Stiftung Wissenschaft und Politik (SWP), 2019)
In December 2018, 152 United Nations (UN) member states adopted the Global Compact for Safe, Orderly and Regular Migration. The document sets out 23 objectives that guide countries of origin, transit and destination in how to deal with the challenges arising in the context of international migration and forced displacement. If practical progress is to be made in the management and organisation of global migration flows, this requires a twofold commitment - internal and external - on the part of the states involved. The German government - just like other governments interested in effective, sustainable and coherent migration policies - should use the Compact to identify further needs for internal reform and to win international partners for strategically selected key issues. The Compact's review process, the core of which is the International Migration Review Forum (IMRF), provides an opportunity for both.
Keywords: 320